Canal operations planner. III: minimizing inequity with delivery performance ratio relaxation - Vries, T.T. de (American Society of Civil Engineers, 2017)
For many large irrigation systems, distributing water equitably is a stated management objective. Canal operations plans specify which canal to operate at what discharge for each irrigation interval to achieve the stated objective. In this study, a function of the Gini index is incorporated in to an integer program that can develop a canal operations plan. In contrast with earlier canal operations planners that minimize inequity, the operations planner presented herein does not constrain the discharge in a canal to a binary integer. Rather, the user can define an allocation cost function that in turn defines the preferred operational range of discharge over which any canal should be operated for any interval. The operations planner can also be modified to permit spillages. The model is applied to a secondary canal in Pakistan, and the sensitivity of the results to operational range and permissible spillage are explored. An engineering application of the model is presented.